Editorial: Between Hope and Hype: Critical evaluations of technology’s role in anti-trafficking - Musto, Jennifer; Thakor, Mitali; Gerasimov, Borislav (Anti-Trafficking Review, 2020)
Over the past decade, scholars, activists, and policymakers have repeatedly called for an examination of the role of technology as a contributing force to human trafficking and exploitation. Attention has focused on a range of issues from adult services websites and the use of social media to recruit victims and facilitate trafficking to the utilisation of data analytics software to understand trafficking and identify ‘hotspots of risk’. This article introduces the Special Issue of Anti-Trafficking Review devoted to the role of technology in (anti-)trafficking. It outlines the main assumptions and critiques some of the proposed ‘solutions’ in the field and presents briefly the articles included in the issue. It concludes that the factors that enable and sustain human trafficking are varied and complex and require political will – not tech solutionist fixes.